The Effect of Productivity, Unemployment, Inflation, and Government Spending on Income Inequality in East Java - Dimas Wahyu Rozaki; Bambang Eko Afiatno (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2024)
Income inequality is an obstacle for Indonesia to try to escapethe middle income trap. Income inequality in the country shows an upward trend, due to low labor productivity, rising unemployment, and inflation. This study aims to examines the effectof labor productivity, unemployment, inflation, and government spending on health and education in districts/cities of East Java province from 2018 to 2023. The results of theoretical testing using the Sys-GMM analysis model explain that labor productivityshows a relationship with the same direction, as well as significant to the Gini index variable, as a measure of income inequality. The number of low-educated workers and dominated by informal sector workers is a strong reason for this phenomenon. The formation of the regional inflation control team proved to be very effective. This can be seen from the absence of a significant effect of inflation on income inequality. The unemployment rate and income inequality shows a relationship with the same direction and significant. Local government efforts through education spending have a significant effect on income inequality, but the positive relationship between the two indicates that education spending targeting primary and secondary non-vocational education takes a long time to affect income inequality. Health spending has a significant effect on lowering income inequality. Regional health insurance programs and worker health monitoring are quite effective in improving the quality of health of the whole society.